The effective role of alkali earth/alkali ratio on formation HCA nano particles for soda lime phospho silicate glass system - P. Kiran; V. Ramakrishna; N.K. Udayashankar; H.D. Shashikala (Elsevier, 2017)
In the present work, we report on the effect of the CaO/Na2O ratio on Non-Bridging Oxygen/Bridging Oxygen (NBO/BO) ratio for sol-gel synthesised 58SiO2-(38-x)CaO-xNa2O-4P2O5 glasses and establish the correlation between Hydroxy Carbonated Apatite layer (HCA) forming ability and the dissolution behaviour in simulated body fluid (SBF) solution. Thermal stabilities were calculated as 221, 135, 153 and 77 °C respectively. It is inferred that thermal stabilities varied nonlinearly with CaO/Na2O ratio. Similarly NBO/BO ratios were obtained using Raman spectroscopic analysis as 0.6293, 0.7917, 0.2264 and 0.3513, respectively. All samples were soaked in the SBF solution for 7 days. The calculated weight losses of these samples were 55.32, 69.13, 18.09 and 20.08 for the corresponding NBO/BO ratios. The decrease in CaO/ Na2O ratio led to nonlinear variation of the NBO/BO ratios. Consequently the non linear variation in NBO/BO ratio led to the nonlinear variation of HCA forming ability of SBF treated samples.